Study on impact of tectonic structure surface on stability of end-slope mining process in open-pit mine - WANG Shufeng; YANG Zhiyong; HU Guilin (Meikuang Anquan, 2022)
Based on the problem of tectonic structural surfaces existing in the end slope of huge thick coal seam open-pit mine, this paper uses the limit equilibrium method and numerical simulation to analyze the influence of tectonic structural surfaces of different sizes and positions on the slope stability during end slope mining. The results show that the existence of tectonic structural surfaces will reduce the stability of end slope, and the longer the structural plane and the closer it is to the bottom of end slope, the greater the impact on slope stability; the structural surface does not affect either the trend of slope stability coefficient variation or the transfer of maximum shear strain increment.